Comparison of oblique and transforaminal approaches to lumbar interbody fusion for lumbar degenerative disease: An updated meta-analysis - Lin, Guang-Xun; Xu, Wen-Bin; Kotheeranurak, Vit; Chen, Chien-Min; Deng, Zhi-Hong; Zhu, Ming-Tao (Frontiers in Surgery, 2023)
Objective: Oblique lumbar interbody fusion (OLIF) and transforaminal lumbar interbody fusion (TLIF) are widely used in the treatment of lumbar degenerative diseases. A meta-analysis was performed to examine the clinical and radiological effects of these two techniques. Methods: A search of relevant literature from several databases was conducted until November 2021. Perioperative outcomes, clinical and radiological results, and complications were analyzed. Results: Fifteen qualified studies were included. OLIF showed a shorter operative time and length of hospital stay and less blood loss than TLIF. Early postoperative Visual Analogue Scale for back pain were significantly lower in OLIF than in TLIF (P = 0.004). Noteworthy, although the preoperative Oswestry Disability Index (ODI) of the OLIF group was higher than that of the TLIF group (P = 0.04), the postoperative ODI was significantly lower (P < 0.05). Radiologically, the results showed that the disc and foraminal heights of OLIF were significantly higher than those of TLIF postoperatively. Moreover, OLIF can restore more segmental lordosis than TLIF in the early postoperative period. Furthermore, OLIF showed better fusion rates than TLIF (P = 0.02), with no difference in cage subsidence (13.4% vs. 16.6%). No significant differences in overall and approach-related complications between the two groups. Conclusion: The OLIF group showed an advantage in terms of operative time, hospitalization, intraoperative blood loss, early back pain relief, postoperative function recovery, disc and foraminal heights, early segmental lordosis, and fusion rate compared to TLIF. For both procedures, the incidence rates of overall and approach-related complications were comparable.